Column Extraction and Separation of Some Metal Ions by Diethylenetriamine Polysiloxane Immobilized Ligand System - Nizam M. El-Ashgar (E-Journal of Chemistry)
An extraction chromatographic solid porous polysiloxane functionalized by chelating diethylenetriamine ligand of the general formula P-(CH2)3-NH(CH2)2NH(CH2)2NH2, (Where P represents [Si-O]n siloxane network) has been evaluated for the separation of Co(II), Ni(II) and Cu(II) from aqueous solutions. The chromatographic parameters of the separation method have been optimized. The ligand system retained Co(II), Cu(II) and Zn(II) effectively when used as a metal ion extractant by controlling the pH value. The ligand system also shows a good separation of a mixture of metal ions Co(II), Ni(II) and Cu(II) when used as chromatographic stationary phase. The optimum separation pH values were 4.5, 4 for Co(II) and Ni(II) respectively, while a solution of 0.1 M HNO3 was used to elute Cu(II). Metal ions were also preconcentrated at pH 5.5. The chemisorbed metal ions were regenerated from the solid extractant using 0.5 M HCl.